Pancasila, Religion, and Democracy in Yudian and Huntington’s Perspectives - Wulansari, Intan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Religion and democracy are two pivotal forces shaping social and political systems worldwide. Specific Background: In Indonesia, the relationship between religion and democracy is further complicated by the centrality of Pancasila as the state ideology, necessitating a nuanced understanding of its interaction with religious values. Knowledge Gap: While numerous studies have addressed religion’s role in politics, few have conducted a comparative analysis between local Islamic scholars and Western political theorists in the context of Pancasila and global dynamics. Aims: This study aims to analyze the perspectives of Yudian Wahyudi and Samuel P. Huntington on the intersection of religion and democracy, highlighting their similarities, differences, and contemporary relevance. Results: Findings show that Yudian conceptualizes religion as an integrative moral foundation that harmonizes with Pancasila through integrative tauhid and maqasid al-shari‘ah, while Huntington emphasizes religion’s ambivalence, viewing it as both a driver of democratization and a source of civilizational conflict. Novelty: The study contributes a comparative framework that bridges Indonesian Islamic thought with global political theories, enriching discourse on democracy and religion. Implications: These insights underscore the importance of prudent management of religion in politics to foster inclusive and sustainable democratic governance in plural societies Highlights: Comparative analysis of local and global perspectives. Religion as both moral foundation and conflict source. Implications for inclusive democratic governance. Keywords: Pancasila, Religion, Democracy, Yudian Wahyudi, Huntington